2021
DOI: 10.1002/mds.28809
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic Pupillometry in Isolated Rapid Eye Movement Sleep Behavior Disorder

Abstract: Background: Melanopsin retinal ganglion cell (mRGC)-mediated pupillary light reflex (PLR) abnormalities have been documented in several neurodegenerative disorders including Parkinson's disease. Overall, isolated rapid eye movement (REM) sleep behavior disorder (iRBD) represents the strongest prodromal risk factor for impending α-synucleinopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…Our findings are consistent with a recent study by Perkins et al [9] that demonstrated that pupil constriction and dilatation in iRBD patients were significantly decreased compared to controls, but were not different from those in PD patients. A decrease in pupillary constriction amplitude in patients with iRBD was also found in a chromatic pupillometry study [10]. Notably, only iRBD patients with positive skin biopsy for α-synuclein deposits showed significant PLR abnormalities compared to controls, supporting that parasympathetic pathways are affected by the underlying α-synucleinopathy in iRBD.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Our findings are consistent with a recent study by Perkins et al [9] that demonstrated that pupil constriction and dilatation in iRBD patients were significantly decreased compared to controls, but were not different from those in PD patients. A decrease in pupillary constriction amplitude in patients with iRBD was also found in a chromatic pupillometry study [10]. Notably, only iRBD patients with positive skin biopsy for α-synuclein deposits showed significant PLR abnormalities compared to controls, supporting that parasympathetic pathways are affected by the underlying α-synucleinopathy in iRBD.…”
Section: Discussionsupporting
confidence: 54%
“…Of the 7 pupillometric parameters in this study, the only difference was the larger pupil diameter before and after light stimulation (PDmax and PDmin) in the PD patients, than that in the RBD patients. Larger baseline pupil diameters in patients with iRBD and PD compared to controls were reported in a few studies [10,21]. Along with the reduced constriction amplitude and delayed latency, they are considered to reflect parasympathetic dysfunction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Immunohistochemical analysis of nerve fibers using primary antibodies that simultaneously allow both to unmask the deposits of phosphorylated α-synuclein and to highlight the presence of specific markers of nerve fibers such as the antibody for the pan-neuronal marker. The superposition of both these markers will allow to establish the intraneuronal deposition of phosphorylated α-synuclein deposits; (ii) salivary alpha-synuclein ELISA analysis; (iii) pupillometry obtained through the use of a pupillometer that evaluates the activity of retinal ganglion cells, evaluating the changes in pupil diameter in relation to light stimuli of different intensity, according to the methods previously described [ 20 22 ]; optical coherence tomography (OCT), obtained using an instrument (Heidelberg Spectralis) which allows, using reflected light, to reconstruct a three-dimensional image of the thickness of the optic nerve; and (iv) genetic investigation from DNA with a screening panel in which all known gene associated with PD and other synucleinopathies are tested, sampled following a specific protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Also, in this study, we used a higher luminance to obtain a cone-driven response than in some previous works (2.4 log cd.m –2 vs. 1 log cd.m –2 ) ( Park et al, 2017 ; Joyce et al, 2018 ; La Morgia et al, 2022 ). However, this luminance is still slightly lower than followed in a protocol previously established by Park et al (2011) , who used 2.6 log cd.m –2 .…”
Section: Discussionmentioning
confidence: 99%